2008
DOI: 10.1016/j.neulet.2007.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric analysis of the TM2 6′ phenylalanine mutation on desensitization in α1β2 and α1β2γ2 GABAA receptors

Abstract: SummaryThe presence of phenylalanine (F) at the 6′ position of transmembrane domain 2 (TM2) in the α4 subunit of α4β2 nicotinic receptors enhances desensitization. As the GABA A receptor affords the ability to study the influence of as few as one and as many as five Fs at this position, we have used it to investigate potential subunit-and stoichiometry-dependent effects of the TM2 6′F mutation on desensitization. Whereas the presence of one F at this position decreased extent of desensitization, desensitizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…BB, GB, DTZ, and PXN inhibition is subunit dependent at the 5-HT 3 receptor, similar to the actions of these compounds at other Cys-loop receptors (Das and Dillon, 2003;Erkkila et al, 2008;Gonzales et al, 2008;Thompson et al, 2011). 5-HT 3 AB receptors were less sensitive to PXN than 5-HT 3 A receptors, and mutation of the 5-HT 3 A 6Ј residue to its B subunit counterpart (T6ЈS) completely abolished inhibition by BB, GB, and PXN.…”
Section: Discussionsupporting
confidence: 52%
“…BB, GB, DTZ, and PXN inhibition is subunit dependent at the 5-HT 3 receptor, similar to the actions of these compounds at other Cys-loop receptors (Das and Dillon, 2003;Erkkila et al, 2008;Gonzales et al, 2008;Thompson et al, 2011). 5-HT 3 AB receptors were less sensitive to PXN than 5-HT 3 A receptors, and mutation of the 5-HT 3 A 6Ј residue to its B subunit counterpart (T6ЈS) completely abolished inhibition by BB, GB, and PXN.…”
Section: Discussionsupporting
confidence: 52%
“…For example, in the ␣1␤ Gly receptor activation by agonists is markedly affected by mutations in the ␣1 subunit, but not in the homologous ␤ mutant subunits (30). In the GABA A receptor, asymmetric contribution of subunits has been reported for permeability (31), effect of gain-of-function mutations (L9Ј and F6Ј) (32)(33)(34) and mutations that ablate pH modulation (35).…”
Section: Discussionmentioning
confidence: 99%
“…The stoichiometry of recombinant ␣ 4 ␤ 2 GABA A Rs was 2␣ 4 :3␤ 2 , whereas the ␣ 1 ␤ 2 GABA A R stoichiometry was 3␣ 1 :2␤ 2 (Table 1). Our previous work, using tandem subunit constructs, also indicated that ␣ 1 ␤ 2 GABA A Rs stoichiometry was 3␣ 1 :2␤ 2 (6), but others have reported a 2␣ 1 :3␤ 2 stoichiometry (38,39), suggesting that both stoichiometries are possible. Studies examining ␣ 6 ␤ 2 GABA A R subtypes report that the subunit stoichiomety is 3␣ 6 :2␤ 2 (40), whereas for ␣ 1 ␤ 3 GABA A Rs the stoichiometry is 2␣ 1 :3␤ 3 (3).…”
Section: Discussionmentioning
confidence: 91%